(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
There is a lot of pressure, stress, and expectations on students in today’s educational system,which makes them feel horrible. These obstacles impede kids’ overall growth and academic success,which lowers their subjective well-being and lowers their level of life pleasure. Therefore, it’s important topromote happy feelings. The effect of Positive Psychology Interventions in boosting students’ positiveemotions and helping them feel happier and more satisfied has been critically reviewed. The goal ofschool psychology has been to identify the issue and provide remedies. Positive feelings are more crucialfor success and wellbeing than the absence of negative feelings. By strengthening positive elementscrucial for success and thriving, in positive psychology therapies, the primary objective is to eradicatethe weak and bring in the strong. Positive psychology interventions have been linked in a major way tostudents’ wellbeing, which may increase life satisfaction, according to research.